2000
DOI: 10.1098/rstb.2000.0683
|View full text |Cite
|
Sign up to set email alerts
|

Hair cell heterogeneity and ultrasonic hearing: recent advances in understanding fish hearing

Abstract: The past decade has seen a wealth of new data on the auditory capabilities and mechanisms of ¢shes. We now have a signi¢cantly better appreciation of the structure and function of the auditory system in ¢shes with regard to their peripheral and central anatomy, physiology, behaviour, sound source localization and hearing capabilities. This paper deals with two of the newest of these ¢ndings, hair cell heterogeneity and the detection of ultrasound. As a result of this recent work, we now know that ¢shes have se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 20 publications
1
18
0
1
Order By: Relevance
“…The greatest sensitivity of yellowfin occurs between 200 and 800 Hz, where the mean thresholds ranged from 89 to 100 dB re 1 µPa. This evidence concurs with that of the vast majority of fish studied to date which appear to have, apart from a few species with specialist hearing, a relatively narrow audible frequency range (Popper 2000). It thus appears reasonable that the experimental bluefin tuna in our study responded mainly to noises falling within the range observed by Iversen (1967).…”
Section: Discussionsupporting
confidence: 79%
“…The greatest sensitivity of yellowfin occurs between 200 and 800 Hz, where the mean thresholds ranged from 89 to 100 dB re 1 µPa. This evidence concurs with that of the vast majority of fish studied to date which appear to have, apart from a few species with specialist hearing, a relatively narrow audible frequency range (Popper 2000). It thus appears reasonable that the experimental bluefin tuna in our study responded mainly to noises falling within the range observed by Iversen (1967).…”
Section: Discussionsupporting
confidence: 79%
“…An invagination of the otic placode to form an otic vesicle is a character of the crown craniate group (Maisey, 1986;Janvier, 1996). The inner ear probably did not evolve from the lateral line, or vice-versa, but both probably arose independently (and at different times) from a loosely-arranged system of superficial neuromast organs or placodes (see also Popper et al, 1992;Popper, 2000).…”
Section: The Craniate Inner Ear From a Phylogenetic Perspectivementioning
confidence: 98%
“…Type II hair cells contact small bouton endings of primary afferent neurites and the outer faces of neighboring calyces (Spoendlin, 1965;Engström, 1970;Ross et al, 1985). Anamniotes (fish and amphibians) such as the toadfish have traditionally been described as having only type II-like elements (Wersä ll, 1960;Flock, 1964;Gleisner et al, 1973), although there is increasing evidence for the existence of a multiplicity of morphologically defined hair cell types in these species (Popper, 2000). The present study was conducted to visualize the three-dimensional spatial distribution of GABA and glutamate immunolabeling in whole mounts of the vestibular labyrinth of the oyster toadfish, to examine the regional distribution of hair cell transmitter phenotype and the relationship between GABAergic and glutamatergic sensory cells.…”
mentioning
confidence: 99%